Kontribusi Strategi Coping Terhadap Compassion Fatigue Pada Perawat di Rumah Sakit Kabupaten Pasaman Barat - Salma Syakira; Rida Yanna Primanita (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
This study aims to determine whether coping strategies contribute to compassion fatigue among nurses at a hospital in West Pasaman Regency. The research employed a quanitative approach using a non-probability sampling technique with saturated sampling. A total of 65 nurses from the ICU, Emergency Departement, and Surgical Unit participated in the study. The measurement instruments were developed by researcher, referring to the coping strategies theory proposed by Amirkhan (1990) and the compassion fatigue scale adapted by Eka and Tahulending (2017). Data analysis was conducted using SPSS version 22 for windows. Based on the result multiple linear regression analysis, coping strategies were found to contribute to compassion fatigue among nurses in the hospital. Specifically, the problem solving and seeking social support dimensions of coping strategies showed a significant contribution to compassion fatigue, while the avoidance strategy did not a significant contribution.